Anthropology - Ember, Carol R.; Ember, Melvin (New Jersey : Englewood Cliffs, 1981)
A new edition is a compliment and a challenge.
One. Introduction to anthropology -- Two. Human evolution: biological and cultural -- Three. Cultural variation -- Four. Culture and anthropology in the modern world.
Includes bibliographical references and index.
Keywords: ANTHROPLOGY